2015
DOI: 10.3126/jcmc.v4i3.11932
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on prevention of complications related to immobility among caregivers of orthopedic patients at selected hospitals of Chitwan district

Abstract: Immobility is a condition in which a person is unable to move freely or is restricted for therapeutic reasons. Immobility affects all systems of the body leading to complications. The objective of the study is to find out the knowledge on prevention of complications related to immobility among caregivers of orthopedic patients admitted on orthopedic ward of Chitwan Medical College Teaching Hospital (CMCTH), College of Medical Sciences Teaching Hospital (CMSTH) and Bharatpur Hospital, Chitwan. The study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…Regarding relationship between caregiver and patient, it is predicted that if the patient were married, wife and mother were the primary caregiver and other family members were rarely involved in the caretaking. The related result was noticed where level of knowledge is statistically signi cant with area of residence, marital status and educational status of respondents [16].…”
Section: Level Of Knowledgementioning
confidence: 94%
See 2 more Smart Citations
“…Regarding relationship between caregiver and patient, it is predicted that if the patient were married, wife and mother were the primary caregiver and other family members were rarely involved in the caretaking. The related result was noticed where level of knowledge is statistically signi cant with area of residence, marital status and educational status of respondents [16].…”
Section: Level Of Knowledgementioning
confidence: 94%
“…It is reported that the knowledge of caregivers regarding bedsore care was inadequate and practices were found to be incorrect [21]. The caregivers had inappropriate information about prevention of complications resulting due to immobility [16]. It is assumed that age group and educational background may be a factor related to this moderate level of knowledge while, the results showed that age and level of education had a highly signi cant relation.…”
Section: Level Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Oleh itu, rawatan hospital juga seharusnya merangkumi pendidikan penjagaan dan rawatan untuk pesakit dan penjaga tentang amalan penjagaan yang betul di rumah. Penjaga memainkan peranan penting dalam menguruskan semua aspek perawatan pesakit (Poudyal, Neupane & Lopchan, 2014). Mereka adalah orang yang selalu bersama pesakit daripada doktor dan jururawat.…”
Section: Kesimpulanunclassified
“…It is estimated that approximately from 1.2 million people are suffering from bedsores it is reported that there are 60,000 deaths annually from complications arising from bedsores [9].…”
Section: Significance Of the Studymentioning
confidence: 99%